PEMANFAATAN TEKNOLOGI INTERNET DALAM BISNIS SUATU PERUSAHAAN E-COMMERCE - Endro Prihastono (Jurnal Ilmiah Dinamika Teknik, 2010)
Internet in business used for the transfer of information, product catalogue, promotion media, electronic letter, boards bulletin, electronic questioner, and list mailing. Internet also can be used to dialogue, to discus, and consultancy with consumer on-line, so that consumer can be entangled by proactive and interactive in scheme, development, marketing, and sale of product. Marketing pass internet there  method, that is and push of pull marketing. Excellence of business strategy able to be obtained from internet global communications and interactive; providing service and information as according to requirement of consumer; improving same  enabling to open market, product, or new service; and also integrate activity on-line. Application of Electronic Commerce there, Business-To-Consumer and of Business-To-Business Commerce. Payment of transaction of electronic commerce arranged in System of Electronic Funds  Transfer of, while data security is arranged by developed Secure Socket Layer become Secure Electronic Transaction. Keyword: Internet, Electronic Commerce, Business